Clinical Complete Remission of An Advanced Gastric Adenocarcinoma After Camrelizumab Plus Chemotherapy Followed by Camrelizumab Plus Capecitabine: A Case Report - Lin, Jieheng; Yang, Jianying; Wang, Wenping; Lin, Xiaotong; Cao, Yang (Frontiers in Oncology, 2021)
We report a rare case of PDL1-negative advanced gastric adenocarcinoma that improved significantly after camrelizumab plus chemotherapy followed by camrelizumab plus capecitabine as first-line therapy. A 65-year-old woman was diagnosed with a gastric adenocarcinoma in 2017 via contrast-enhanced computed tomography (CT) and endoscopic biopsy. She stabilised after preoperative neoadjuvant chemotherapy, surgery, and postoperative adjuvant chemotherapy. In September 2019, positron emission tomography (PET)/CT re-examination suggested a peritoneal metastasis and multiple lymph node metastases. She then received six cycles of camrelizumab plus chemotherapy. PET/CT indicated that the metastatic foci had disappeared and that she had achieved a clinical complete response（CCR）. She was followed-up with camrelizumab plus capecitabine (maintenance therapy). At the time of writing, her progression-free survival is more than 14 months and her quality of life is good. Thus, camrelizumab plus chemotherapy is a useful first-line treatment for HER2- and PD-L1-negative advanced gastric adenocarcinoma.